Educação e culturas juvenis: o rap no contexto escolar - Santos, Mayara dos (2018)
This paper analyzes teachers and high school student’s perception from state high schools of Cascavel-PR, Brazil, about the possible relations between education and youth cultures, most specifically using rap in the school context to avoid view indifference in learning and school dropout at this stage of education. Rap is the emerging musical genre of hip hop movement, and it is described in this research as a sign of identification among young people and an articulating element of tribes and youth cultures. Rap is also part of the socialization processes of the youth, being full with meanings that integrate the sharing of feelings through this symbolism, the music. It is known that the valuation of different forms of aggregation, having as principle the sharing of feelings, is one of the characteristics of postmodern societies. Postmodernity marks the period of valorization of heterogeneity, multiculturalism and the recognition of different forms of aggregation, and it has as principle the socialization of common interests linked to affective issues. Therein, understanding that postmodernity provided new insights, regarding youth and youth groups, this research implies a reflection on the school as a dynamic social environment, constituting a space of interchange between different tribes and youth cultures. In this way, this paper points out aspects that make it difficult and / or possible to diversify methodologies in classroom, taking as reference issues of daily life and, especially, youth cultures. We believe that this can be an efficient way to reduce rates of school dropout and disinterest in learning from high school students, considering that one of the biggest complaints of young people is the difficulty of establishing relations between content and everyday life. The research was carried out in two stages: bibliographical and field research. The bibliographical research deals with the study of authors who approach the subject of postmodernity, youth, youth cultures, urban tribes, as well as data analysis related to school dropout and lack of interest in learning about the theme of youth and their relationship with the school, establishing a panorama of the phenomenon in Brazil, Paraná state and the city of Cascavel. The field research includes the data collected from ten teachers and students interviews from two high schools in the city of Cascavel. The interviews questioned about youth, school dropout, learning interest and the use of rap in school. The analysis of the data is based on the assumptions of Phenomenology by Michel Maffesoli. It was possible, through this research, to perceive that the students, in general, point out that using rap as an educational instrument that is articulated to the curricular contents can be a means of fostering interest in learning. On the other hand, while most teachers claim that rap can actually be considered an educational tool used in class and contributes to students' interest in learning, just a few have actually used it to work as educational content. This leads us to understand that, although there is an understanding that rap is an educational tool and collaborates in the apprehension of the curricular contents and arouses the interest for learning, this ends up being more a discourse than in fact a practice, because the teachers do not use it as their pedagogical practice.